Satisficing in strategic environments: a theoretical approach and experimental evidence - Werner Güth; Maria Vittoria Levati; Matteo Ploner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
The satisficing approach is generalized and applied to finite n-person games. Based on direct elicitation of aspirations, we formally define the concept of satisficing, which does not exclude (prior-free) optimality but includes it as a border case. We also review some experiments on strategic games illustrating and partly supporting our theoretical approach.
Keywords: C72; C92; D01; 330; Strategic interaction; satisficing behavior; bounded rationality; Beschränkte Rationalität; Nichtkooperatives Spiel; Test